PROFIL PENYELESAIAN SOAL HIGHER ORDER THINKING SKILLS SISWA KELAS VIII SMP NEGERI MODEL TERPADU MADANI PALU PADA MATERI POLA BILANGAN : The Profile of Solving Higher Order Thinking Skiils Questions in Grade VIII Students at SMP Negeri Model Terpadu Madani Palu on Number Pattern Material - Seftiani, Dini; Murdiana, I Nyoman (Aksioma, 2025)
This research aims to obtain a description of the higher order thinking skills problem solving profile of class VIII Raden Saleh students at Madani Integrated Model State Middle School in Palu on Number pattern material. This type of research is qualitative decriptive research. The subjects in this study consisted of 3 students, of which 1 student had high mathematics ability, 1 student had moderate mathematics ability, and 1 student had los mathematics ability. Data collection techniques use test and interviews. Data analysis uses 3 stages, namely data reduction, data presentation, and drawing conclusions. The results showed that subjects with high mathematical ability achieved four indicators of solving number pattern problems based on HOTS questions, subjects with moderate mathematical ability achieved four indicators of solving number pattern problems based on HOTS questions but there were several indicators that werw not completed well, and subjects eith high mathematical ability low mathematics achieved three indicators of solving number pattern questions based on HOTS questions and There were indicators that were not completed.